Professor Henry Urich 1916–2015: A London neuropathologist and his Polish heritage. (February 2020) - Karch, Steven B; Swash, Michael
This is the story of a tumultuous life, lived with enthusiasm and considerable academic success, despite destruction of his cultural heritage in Poland, and loss of his family, by the cruelty of the invading Soviet and Nazi armies in 1939. As a newly qualified doctor from the Polish Medical School at the University of Edinburgh, he was parachuted into Arnhem with the Polish airborne forces, survived, educated himself in British ways and habits, and rapidly succeeded in the medical hierarchy to become an esteemed neuropathologist not only at The London Hospital, but internationally. His central European background provided him with the linguistic and multicultural skills to excel in this highly specialised area of medical science. He was one of the last of the classically trained neuropathologists.